2013
DOI: 10.4172/2155-9880.s4-002
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Different Natural and Synthetic Biomaterials to Support Cardiomyocyte Growth

Abstract: The aim of this study was to scan through several biomaterials to find an optimal biomaterial to support the growth of cardiomyocytes. Neonatal rat cardiomyocytes were cultured on polylactide, chitosan, poly (1,8-octanediolco-citric acid), copolymer of poly(ethylene oxide terephthalate) and poly (butylene terephthalate), PuraMatrix™ and collagen. The suitability of biomaterials for cardiomyocyte culture was evaluated based on several parameters. The cells were characterized with time-lapse imaging, immunocytoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…In general, collagen hydrogels have been shown to support cardiomyocyte survival and formation of a 3D network within the hydrogels. 59 Taken together, our results suggest that (a) collagen concentration plays an important role in cardiomyocyte survival, with higher concentration possibly resulting in less porosity, thereby decreasing cell survival and (b) mixing 2 mg mL 21 collagen scaffolds with ECM proteins might not offer additional benefit to cardiomyocyte survival.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…In general, collagen hydrogels have been shown to support cardiomyocyte survival and formation of a 3D network within the hydrogels. 59 Taken together, our results suggest that (a) collagen concentration plays an important role in cardiomyocyte survival, with higher concentration possibly resulting in less porosity, thereby decreasing cell survival and (b) mixing 2 mg mL 21 collagen scaffolds with ECM proteins might not offer additional benefit to cardiomyocyte survival.…”
Section: Resultsmentioning
confidence: 63%
“…Evans et al noted similar effects of fibronectin and laminin substrates on embryonic and neonatal cardiomyocyte survival wherein, 2D fibronectin substrates and collagen type‐I (2D substrates or 3D scaffolds) provided greater than 85% cell survival, while 2D laminin substrate allowed for only 55% cell survival. In general, collagen hydrogels have been shown to support cardiomyocyte survival and formation of a 3D network within the hydrogels . Taken together, our results suggest that (a) collagen concentration plays an important role in cardiomyocyte survival, with higher concentration possibly resulting in less porosity, thereby decreasing cell survival and (b) mixing 2 mg mL − 1 collagen scaffolds with ECM proteins might not offer additional benefit to cardiomyocyte survival.…”
Section: Resultsmentioning
confidence: 65%
“…In our previous study [14], we showed that the growth of NRCs was best supported by natural collagen. Therefore, we wanted to continue our studies using a material with properties similar to those of natural collagen.…”
Section: Discussionmentioning
confidence: 99%
“…Scaffold-free human cardiac tissue has also been generated [13]. In our previous studies, we compared different synthetic and natural biomaterials for their ability to support cardiomyocyte growth [14]. Of the biomaterials we tested, natural collagen supported cardiomyocyte growth the best but showed significant batch-to-batch variation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation